Improving Teacher's Innovative Work Behavior Through Permanent Teacher's Foundation In Private High Schools In Cibinong District, Bogor District - Edianto, Engkom; Karmila, Nita; Istiadi, Yosa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This study aims to determine the relationship between personality, empowerment, and self-efficacy with teachers' innovative work behavior using technical analysis of correlation regression and Sitorem analysis. The research was conducted at private high school (SMA) teachers in Cibinong district. The research population consisted of 218 teachers with a total sample of 141 teachers. Using the Slovin formula with an error tolerance of 5%. Data collection using a questionnaire. Technical data analysis using correlation regression analysis and SITOREM analysis. The results showed: First, there was a positive relationship between personality and teacher's innovative work behavior with a correlation value of 0.712 and a significance value of the t test = 0.000 (p 0.05). Second, there is a positive relationship between empowerment and teachers' innovative work behavior with a correlation value of 0.657 and a significance value of the t test = 0.000 (p 0.05). Third, there is a positive relationship between self-efficacy and teachers' innovative work behavior with a correlation value of 0.427 and a significance value of the t test = 0.000 (p 0.05). Fourth, there is a positive relationship between personality and empowerment simultaneously with teachers' innovative work behavior with a correlation value of 0.733 and a significance value of the F test = 0.000 (p 0.05). Fifth, there is a positive relationship between personality and self-efficacy simultaneously with teachers' innovative work behavior with a correlation value of 0.734 and a significance value of the F test = 0.000 (p 0.05). Sixth, there is a positive relationship between empowerment and self-efficacy simultaneously with teachers' innovative work behavior with a correlation value of 0.676 and a significance value of the F test = 0.000 (p 0.05). Seventh, there is a positive relationship between personality, empowerment, and self-efficacy simultaneously with teachers' innovative work behavior with a correlation value of 0.746 and a significance value of the F test = 0.000 (p 0.05).